Morphometry of isthmus of thyroid gland in bangladeshi cadaver. - Sultana, SZ; Khalil, M; Khan, MK; Rahman, MM; Mannan, S; Wahed, F; Choudhury, S (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):366-370 The abstract of this article is available on the PubMed website